The Development of First Line Nurse Manager Competency Scale, Medpark Hospital - Intachit, Pranpanita; Angsuroch, Yupin (Vajira Nursing Journal, 2024)
This descriptive research aimed to study the competencies of first line nurse managers at MedPark Hospital, develop a competency assessment tool, and evaluate the quality of this tool for junior nursing managers. The development of the competency assessment tool involved a literature review, studying the vision and mission of MedPark Hospital, and conducting focus group discussions with 10 experts. The result was a set of core competencies, sub-competencies, and behaviors for assessment using a rating scale. The research findings revealed that the competencies of first line nurse managers at MedPark Hospital comprised five key areas with a total of 20 sub competencies as follows leadership competency 5 sub-competencies, expertise competency 4 sub-competencies, communication and health technology competency 3 sub-competencies, resource management competency 4 sub-competencies and business management competency 4 sub-competencies. The quality of the assessment tool, specifically the Index of Item-Objective Congruence (IOC), was evaluated by three experts in nursing management from private hospitals, achieving a score of 0.76. The assessment tool was then piloted (try out) with a sample group like the actual study population, consisting of 30 individuals including supervisors, junior nursing managers who conducted self-assessments, colleagues, and subordinates. The data obtained were used to calculate the cronbach's alpha coefficient, resulting in a score of 0.90. Additionally, the reliability analysis of the population group consisting of 126 individuals yielded a reliability score of 0.88.